ANALISIS KARAKTER DAN LATAR PADA CERPEN “JANJI SANG PENARI” KARYA NYOMAN TUSTHI EDDY - Sinta Sinta; Wikanengsih Wikanengsih; Agus Priyanto (IKIP Siliwangi, 2021)
This study aims to examine the characters and settings in Nyoman Tusthi Eddy's short story